2021
DOI: 10.1093/occmed/kqab057
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination intent among London healthcare workers

Abstract: Background The 10-month timeline from conception to regulatory approval of the Pfizer–BioNTech vaccine against SARS-CoV-2 is unprecedented in modern medicine. However, the climate of the pandemic has also seen anti-vaccination sentiments flourish. Aims To determine the intent to accept COVID-19 vaccination among healthcare workers at a London Hospital Trust and examine variation in uptake between demographic groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 6 publications
3
30
2
Order By: Relevance
“…Biswas et al in their review of 35 available studies published until February 2021 revealed that the prevalence of COVID-19 vaccination hesitancy in HCWs worldwide ranged from 4.3 to 72% (average = 22.51% across all studies with 76,471 participants) [ 12 ]. A recent French multicenter study by Janssen et al ( n = 4349) noted that at least 22% of HCWs working in a hospital were not planning to get vaccinated at all [ 13 ], a study by Abuown et al ( n = 514) set this value at 24% in a London hospital [ 14 ]. Most of the studies found that individuals who were males, of older age, and doctoral degree holders (i.e., physicians) were more likely to accept COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biswas et al in their review of 35 available studies published until February 2021 revealed that the prevalence of COVID-19 vaccination hesitancy in HCWs worldwide ranged from 4.3 to 72% (average = 22.51% across all studies with 76,471 participants) [ 12 ]. A recent French multicenter study by Janssen et al ( n = 4349) noted that at least 22% of HCWs working in a hospital were not planning to get vaccinated at all [ 13 ], a study by Abuown et al ( n = 514) set this value at 24% in a London hospital [ 14 ]. Most of the studies found that individuals who were males, of older age, and doctoral degree holders (i.e., physicians) were more likely to accept COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Biswas et al conclude in their review that the majority of studies found concerns about vaccine safety, efficacy, and potential side effects as top reasons for COVID-19 vaccination hesitancy [ 12 ]. Safety concerns were the dominant reason for vaccine rejection along with doubts about the availability of trial data and vaccine efficacy in the study by Abuown et al [ 14 ]. Moreover, Szmyd et al revealed as the main concern the development of long-term side effects after getting the COVID-19 vaccine [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concerns cited by the respondents with regard to the COVID-19 vaccines were largely shared with participants in other studies [16][17][18]24]. To counteract these concerns, it may be helpful to highlight what is known so far about the adverse effects of COVID-19, so that people can weigh the risks and benefits of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Res. Public Health 2021, 18, 6688 2 of 14 rate among HCW was estimated to be 0.05 cases per 100,000 population of the country. With 0.35 cases per 100,000 population, Italy has shown the highest mortality rate among HCWs in Europe [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation